Effects of acute administration of mazindol on brain energy metabolism in adult mice. Issue 3 (19th September 2013) - Gonçalves, Cinara Ludvig; Scaini, Giselli; Rezin, Gislaine Tezza; Jeremias, Isabela Casagrande; Bez, Gisele Daiane; Daufenbach, Juliana Felipe; Gomes, Lara Mezari; Ferreira, Gabriela Kozuchovski; Zugno, Alexandra Ioppi; Streck, Emilio Luiz
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Mazindol is a sympathomimetic amine, widely used as an anorectic agent in the treatment of obesity. This drug causes psychostimulant effects because of its pharmacological profile similar to amphetamine, acting like a monoamine reuptake inhibitor. However, the mechanisms underlying the action of mazindol are still not clearly understood. Methods Swiss mice received a single acute administration of mazindol (0.25, 1.25 and 2.5 mg/kg, ip) or saline. After 2 h, the animals were killed by decapitation; the brain was removed and used for the evaluation of activities of mitochondrial respiratory chain complexes, Krebs cycle enzymes and creatine kinase. Results Acute administration of mazindol decreased complex I activity only in the hippocampus. Complex IV activity was increased in the cerebellum (2.5 mg/kg) and cerebral cortex (0.25 mg/kg). Citrate synthase activity was increased in the cerebellum (1.25 mg/kg) and cerebral cortex (1.25 mg/kg), and creatine kinase activity was increased in the cerebellum (1.25 mg/kg). Conclusion We suggest that the inhibition of complex I in the hippocampus only and activation of complex IV, citrate synthase and creatine kinase occurs because of a stimulus effect of mazindol in the central nervous system, which causes a direct impairment on energy metabolism.